Cognitive profile and activities of daily living: 35 patients with alpha‐mannosidosis. Issue 6 (28th May 2015) - Borgwardt, L.; Thuesen, A. M.; Olsen, K. J.; Fogh, J.; Dali, C. I.; Lund, A. M.
Abstract: Background: Alpha‐mannosidosis (OMIM 248500) (AM) is a rare lysosomal storage disease caused by a deficiency of the alpha‐mannosidase enzyme. The typical signs consist of hearing impairment, intellectual disabilities, coarse facial features and motor function disturbances. We report on the cognitive function and activities of daily living in patients with AM. Methods: Thirty five AM patients, age 6‐35 years, were included in the study. As a cognitive function test, we used the Leiter international performance scale–revised (Leiter‐R), which consists of two batteries: the visual function and reasoning battery and the memory and attention battery, the latter including a memory screening. Additional two questionnaires, The Childhood Health Assessment Questionnaire (CHAQ) and EQ‐5D‐5 L, were filled out. Results: We found IQ in the range of 30‐81 in our cohort. The total equivalent age (mental age) was significantly reduced, between 3‐9 years old for the visual function and reasoning battery, between 2.3‐10.2 years for the memory screening. Data suggested a specific developmental profile for AM with a positive intellectual development until the chronological age 10‐12 years, followed by a static or slightly increasing intellectual level. All patients were to varying degrees socially and practically dependent and unable to take care of themselves in daily life. Conclusions: Intellectual disability is a consistent finding in patients with alpha‐mannosidosis but with extensive variation. We assess that this group of patients has, despite their intellectual disabilities, a potential for continuous cognitive development, especially during childhood and early teenage years. This should be included and supported in the individual educational planning.